A Visualized Bibliometric Analysis of Translation Studies of Mo Yan’s Works Using VOSviewer from 2000 to 2024 - Qian Wu; Yue Xi (Journal of Linguistics and Communication Studies, 2024)
Mo Yan’s works hold a significant position in the global literary field, and the study of the translations of these works is considered a key approach to promoting literary cross-cultural communication and academic discussions in translation studies. This study, based on the journal articles in the CNKI database from 2000 to 2024, employs the software VOSviewer to carry out a visualized bibliometric analysis. The aim is to illustrate the annual publication volume, co-authorship, co-occurrence clustering of keywords, and the evolutionary trends. The results indicated that the research of translation studies of Mo Yan’s works in China has gone through a process from slow start to rapid growth, with a recent decline in the number of publications followed by a gradual stabilization. A stable core research community has not yet formed. The primary areas of research interest are concentrated on translation strategies within theoretical frameworks, case studies of translators like Howard Goldblatt, and the global circulation and reception of Mo Yan’s literary works. This study provided references for entry into the translation studies of Mo Yan’s works and identifying future research directions.